Can adoption of improved seed varieties spur long-term food security in Malawi? - Salonga, D. T.; Khonje, M. G.; Matchaya, Greenwell C. (Springer, 2024)
Adoption of improved seed varieties (ISV) is considered one of the key ingredients to sustainably increase crop yields and incomes and reducing hunger. Previous research has extensively demonstrated that there is a positive link between adoption of ISV and several agricultural and health outcomes. However, most prior research focused on a single crop only, particularly maize, yet most smallholder farmers grow multiple crops simultaneously. Additionally, most of the existing studies are largely case studies using cross-sectional data, where controlling for possible unobserved confounding factors is difficult. We attempt to address these caveats by testing the hypothesis that adoption of ISV improves crop productivity and income, dietary diversity, and short-term child nutrition outcomes. To do so, we use a decade (2010–2020) of nationally representative panel data from Malawi. Our panel data regression results show that adoption of ISV is positively correlated with value of crop production, dietary diversity, and weight for age z-scores. Our findings suggest that intensifying development and promoting use of nutrition-sensitive ISV among smallholder farming households could be key to sustainably address food insecurity and child malnutrition.